Silencing by nuclear matrix attachment distinguishes cell-type specificity: association with increased proliferation capacity - Linnemann, Amelia K. (Oxford University Press, 2009)
DNA loop organization by nuclear scaffold/matrix attachment is a key regulator of gene expression that may provide a means to modulate phenotype. We have previously shown that attachment of genes to the NaCl-isolated nuclear matrix correlates with their silencing in HeLa cells. In contrast, expressed genes were associated with the lithium 3,5-diiodosalicylate (LIS)-isolated nuclear scaffold. To define their role in determining phenotype matrix attached regions (MARs) on human chromosomes 14–18 were identified as a function of expression in a primary cell line. The locations of MARs in aortic adventitial fibroblast (AoAF) cells were very stable (r = 0.909) and 96% of genes attached at MARs are silent (P < 0.001). Approximately one-third of the genes uniquely expressed in AoAF cells were associated with the HeLa cell nuclear matrix and silenced. Comparatively, 81% were associated with the AoAF cell nuclear scaffold (P < 0.001) and expressed. This suggests that nuclear scaffold/matrix association mediates a portion of cell type-specific gene expression thereby modulating phenotype. Interestingly, nuclear matrix attachment and thus silencing of specific genes that regulate proliferation and maintain the integrity of the HeLa cell genome suggests that transformation may at least in part be achieved through aberrant nuclear matrix attachment.